1987
DOI: 10.1007/bf00031738
|View full text |Cite
|
Sign up to set email alerts
|

The soil water regime in a young radiata pine plantation in southeastern Australia

Abstract: Application. High initial growth rates in plantations may not be sustained beyond canopy closure, when rainfall is insufficient to recharge the soil profile, or restore groundwater to accessible levels. A judicious balance of fertilization, and crop density modified by early thinning, may be necessary to achieve optimum crop productivity and health. A two-year fallow period may be required following felling a mature crop, to allow full recharge of soil water reserves.Abstract. The soil water regime from planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…No studies in south-eastern Australia have measured evapotranspiration in the period of the rotation between harvesting of one tree crop and establishment of the canopy of the next. In south-eastern South Australia, Mitchell and Correll (1987) observed that the soil water profile fully recharged in the 1-year fallow period between the first and second rotation P. radiata plantation, indicating the possibility of some groundwater recharge during this period. More research is needed if recharge during this period of each rotation is to be quantified and the net water balance over a full rotation estimated accurately.…”
Section: Groundwater Recharge Under Plantationsmentioning
confidence: 96%
“…No studies in south-eastern Australia have measured evapotranspiration in the period of the rotation between harvesting of one tree crop and establishment of the canopy of the next. In south-eastern South Australia, Mitchell and Correll (1987) observed that the soil water profile fully recharged in the 1-year fallow period between the first and second rotation P. radiata plantation, indicating the possibility of some groundwater recharge during this period. More research is needed if recharge during this period of each rotation is to be quantified and the net water balance over a full rotation estimated accurately.…”
Section: Groundwater Recharge Under Plantationsmentioning
confidence: 96%
“…1) and causes recurring soil water deficits when trees experience water stress Benyon and Doody, 2004). Depending on the depth of soil, growth rates and the timing of canopy closure (age 5-7 years) radiata pine water use becomes dependant on current rainfall (Mitchell and Correll, 1987;Benyon and Doody, 2004).…”
Section: Sites Soils and Management Historymentioning
confidence: 99%
“…In dry and semi-arid Mediterranean territories, lack of water is the most limiting factor for reconstructing ecosystems [16]. Therefore, it is essential for seedlings to develop a root system as quickly as possible to escape from soil desecation [4,12,15], especially during the first summer after planting. Plantation success also depends on this.…”
Section: Quercus Rotundifolia Pinus Halepensismentioning
confidence: 99%